Oral Health Literacy and Periodontal Disease in Primary Health Care Users - Fernanda Maria Rovai Bado; Taís de Souza Barbosa; Gustavo Hermes Soares; Fábio Luiz Mialhe (Elsevier, 2022)
Background: Oral health literacy (OHL) is a key factor for reducing inequalities in oral health and promoting better health outcomes, including those related to periodontal health. This study aimed to evaluate associations between OHL and periodontal disease amongst users of primary health care services. Methods: This cross-sectional study was carried out with a sample of 250 adult users of primary health care services in Brazil. OHL was measured using the Oral Health Literacy Instrument-Brazilian (OHLA-B). Participants also answered a structured questionnaire addressing sociodemographic and behavioural data. Clinical oral examination was performed using the Community Periodontal Index. Analyses of the crude associations were performed by simple logistic regression models, and estimates were reported as odds ratios (ORs) and corresponding 95% confidence intervals (CIs). Variables associated with a significance level <0.20 in bivariate analyses were included in hierarchical multiple logistic regression models. Results: Amongst participants, 62% were female with an average age of 37.2 years. Adults aged 37 years or older (OR, 5.48; 95% CI, 2.68-11.21), with fewer years of study (OR, 3.34; 95% CI, 1.66-6.71), with low OHL levels (OR, 5.91; 95% CI, 1.71-20.49), and who smoked (OR, 3.29; 95% CI, 1.34-8.09) were more likely to have periodontal pockets compared to their counterparts. Conclusions: Primary health care users with low OHL levels presented with more severe periodontal diseases.